Dynamic demand-side management with user's privacy concern in residential community - Hsin-Hui Kuo; Pradhan, Sipun Kr; Chao-Lin Wu; Pei-Hsuan Cheng; Yifei Xie; Li-Chen Fu (IEEE International Conference on Automation Science and Engineering (CASE), 2016)
In smart grids, demand-side management (DSM) plays an important role between customers and utility company, since it can reduce the total electricity cost of each customer meanwhile alleviate the aggregate peak-to-average ratio (PAR) of utility of a community of customers subject to real-time pricing (RTP) policy. Moreover, a good DSM system should also be able to react quickly when users do not take its advice or when the environment state changes. This works aims at making the DSM system dynamic, which means that the proposed DSM can reschedule the order of activities in nearly real-time whenever original schedule is no longer feasible due to the aforementioned situations. In our problem formulation, each home is assumed to connect to a renewable energy resource, say, photovoltaic (PV) system, and equipped with an energy storage device so that the scheduling can be made more flexible. Thus, besides the case where the original recommended schedule is not followed by the user, another case where the solar power distribution changes from what was predicted also initiates the rescheduling under the dynamic DSM. In addition, for a residential community composed of multiple homes, keeping the privacy of lifestyle for each home is also an issue as important as the energy saving, and therefore a cooperative game is also formulated so as to transfer only the necessary information but hide all the details of power consumption of each home. The simulation results show that the proposed DSM system not only reduce the cost in individual home but also reschedule quickly whenever there is a need, while make a tradeoff between cost and PAR with privacy concern in a residential community.